Spatial patterns of new leprosy cases in a northeastern state of Brazil, 2011-2021 - Maria Luiza Ferreira Imburana da Silva; Shirlley Jackllanny Martins de Farias; Amanda Priscila de Santana Cabral Silva; Maria Olívia Soares Rodrigues; Emília Carolle Azevedo de Oliveira (Associação Brasileira de Pós-Graduação em Saúde Coletiva, 2023)
ABSTRACT Objective: To analyze the spatial patterns of leprosy in Pernambuco from 2011 to 2021. Methods: This is an ecological epidemiological study, carried out with data from the Notifiable Diseases Information System, based on new cases of leprosy among inhabitants of Pernambuco, between 2011-2021. An empirical Bayesian analysis of local and spatial dependence was performed with the global and local Moran indices. Results: 25,008 new cases of leprosy were registered with an annual case detection rate in the general population of 16.51 cases/100,000 inhabitants - which is considered high. Among those younger than 15 years of age, there were 5.16 cases/100,000 inhabitants (high) and 0.89/100,000 inhabitants with degree II of physical disability (low); there were also many high-risk cases with an overall Moran index of 0.33 (p<0.001), active transmission (0.26; p<0.001), and subsequent diagnosis of the disease (0.12; p<0.006), as well as distribution in macro-region 1 and macro-region 4. Conclusion: There was a heterogeneous spatial distribution in the state, showing two overviews, the first being the presence of municipalities with high risk of disease transmission and the second with clusters of silent municipalities, reinforcing the character of leprosy neglect as a major public health problem. This study brings reflections for leprosy control actions, due to the identification of priority areas to combat this disease in Pernambuco.